SAT0748-HPR Working with a musculoskeletal disorder – a qualitative study of workers' experiences. (15th June 2017) - Cochrane, A; Rothwell, CJ; FitzGerald, O; Gallagher, P; Ashton, J; Breen, R; Brennan, A; Corcoran, O; Desmond, D
Abstract : Background: Musculoskeletal disorders (MSDs) are the leading cause of temporary and permanent work related disability across Europe, yet many people are able to remain at work. Objectives: To explore perceived facilitators and barriers to staying at work amongst people experiencing MSD. Methods: Semi-structured interviews conducted with 19 individuals who had attended musculoskeletal assessment clinics in three Irish hospitals within the preceding year with a confirmed diagnosis of non-inflammatory musculoskeletal disorder. Participants were only included if they had been in paid employment continuously for at least six of the previous 12 months. The interviews were audio-recorded and transcribed. Data were analysed using thematic analysis. Results: Participants ranged in age from 21 to 50 years, most were female (n=16). Fifteen participants were continuing to work, while experiencing pain and some functional limitations. Job control emerged as a key factor in continued work participation, specifically, being able to organise workload and make modifications to work practices enabled participants to maintain an acceptable level of work performance. The value of work, both personal and financial, motivated people to continue to work. While some co-workers and supervisors were considered to be helpful, interviewees were concerned that they could lose their job if they asked for assistance or took time off work. Fatigue had a considerable impact on life outside of work, with interviewees reporting effects on family life and reduced participation in social activities. Conclusions: While continuing to work was beneficial, negative spillover effects on life outside of work were commonly reported. Workers with MSD may benefit from interventions that focus on coping with pain and fatigue management, as well as those that raise awareness amongst employers. Acknowledgements: This research is funded by the Health Research Board [RCQPS-2014–2]. Disclosure of Interest: None declared